The Influence of OCEAN as Educational Media to Improve Students' Vocabulary - Prastiwi, Afita Dewi; Saktiono, Maxima Ari; Wijaya, Yudha Hadi (IJET (Indonesian Journal of English Teaching), 2024)
Media as an important part of English teaching has been developed massively. The role of media in teaching English cannot be separated from students and teachers. This study aims to measure the effect of media that has been developed by the writer in order to know the effectiveness of the media itself in improving students’ vocabulary. OCEAN is a media development that provide some features to improve students’ English skill. This study implemented and tested OCEAN to measure the effectiveness of the media. This study used experimental quantitative research and T-test to gain and analyze the data. The result said that the average value of English vocabulary from pre-test is 65.81 ± 5.19, which is lower than the average value of English vocabulary in the post-test, which is 82.12 ± 5.86. To find out whether there is a significant increase in the average variable value of English vocabulary from the pre to post, the Wilcoxon test was carried out. From the Wilcoxon test, it was found that the calculated Z value was smaller than the -Z table (-4,594 < -1,960), and the p-value was smaller than α (0,000 < 0,050), so the decision was taken that H0 was rejected, which means that there is a significant difference in the average between pre and post-test. The conclusion of this study showed that the media is effective in teaching English vocabulary.